Intracytoplasmic-membrane development in alphaproteobacteria involves the homolog of the mitochondrial crista-developing protein Mic60 - Muñoz-Gómez, Sergio A; Cadena, Lawrence Rudy; Gardiner, Alastair T; Leger, Michelle M; Sheikh, Shaghayegh; Connell, Louise B; Bilý, Tomáš; Kopejtka, Karel; Beatty, J Thomas; Koblížek, Michal; Roger, Andrew J; Slamovits, Claudio H; et al. (Current biology, 2023)
Mitochondrial cristae expand the surface area of respiratory membranes and ultimately allow for the evolutionary scaling of respiration with cell volume across eukaryotes. The discovery of Mic60 homologs among alphaproteobacteria, the closest extant relatives of mitochondria, suggested that cristae might have evolved from bacterial intracytoplasmic membranes (ICMs). Here, we investigated the predicted structure and function of alphaproteobacterial Mic60, and a protein encoded by an adjacent gene Orf52, in two distantly related purple alphaproteobacteria, Rhodobacter sphaeroides and Rhodopseudomonas palustris. In addition, we assessed the potential physical interactors of Mic60 and Orf52 in R. sphaeroides. We show that the three α helices of mitochondrial Mic60's mitofilin domain, as well as its adjacent membrane-binding amphipathic helix, are present in alphaproteobacterial Mic60. The disruption of Mic60 and Orf52 caused photoheterotrophic growth defects, which are most severe under low light conditions, and both their disruption and overexpression led to enlarged ICMs in both studied alphaproteobacteria. We also found that alphaproteobacterial Mic60 physically interacts with BamA, the homolog of Sam50, one of the main physical interactors of eukaryotic Mic60. This interaction, responsible for making contact sites at mitochondrial envelopes, has been conserved in modern alphaproteobacteria despite more than a billion years of evolutionary divergence. Our results suggest a role for Mic60 in photosynthetic ICM development and contact site formation at alphaproteobacterial envelopes. Overall, we provide support for the hypothesis that mitochondrial cristae evolved from alphaproteobacterial ICMs and have therefore improved our understanding of the nature of the mitochondrial ancestor.
Keywords: Mitochondrial Membranes; biologická evoluce; mitochondriální membrány; MICOS; mitochondrie; Cereibacter; eukaryote; Rhodopseudomonas; eukaryogenesis; mitochondriální proteiny; Biological Evolution; Mitochondria; Alphaproteobacteria; endosymbosis; purple bacteria; Rhodobacter; Mitochondrial Proteins; chromatophores